Do Different People Believe in a Just World Differently? Study of it Specialists in the Context of the Russian Invasion of Ukraine - Kryazh, Iryna; Kholmanova, Viktoriya (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2025)
The current study utilized cluster analysis to investigate the different configurations of Personal Belief in a Just World (PBJW) and General Belief in a Just World (GBJW) among Ukrainian IT -specialists and explored how these distinct justice belief profiles relate to Subjective Well-being (SWB), encompassing life satisfaction (SWL) and emotional well-being (SSWB) and Existential Fulfillment (EF) in the dramatically shifted context from peacetime (2021) to wartime (2022). This approach provided insight into the functioning of this established psychological resource under conditions of extreme uncertainty and military aggression. Sample:177 IT-specialists (86 men, 71 women): 80 during 2021 peacetime, 77 in 2022, after Russia’s invasion. Methods: Belief in a Just World scale (Dalbert, 1999), Test of Fundamental Motivation (Eckhardt, 2001), Satisfaction With Life Scale (Diener et al., 1985), Scale of Subjective Well-being (Perrudet-Badoux et al., 1988). Foundlings: The study identified five distinct profiles of personal and general justice beliefs, showing that these components do not always coincide. The findings confirmed the adaptive role of PBJW for well-being and highlighted a compensatory function of GBJW under wartime conditions. By examining BJW profiles across peaceful and wartime periods, the study expands existing evidence by demonstrating both the stability of these profiles and their sensitivity to major societal disruptions.